Peningkatan Daya Saing UMKM Berbasis Digital: Implementasi Pembukuan dan Pembayaran Digital - Arifin, Farid; Saputra, Shandika Aditya; Choir, Algeri Yusuf Ahmad; Devi, Zahwa Kumara; Al Bilqis, Valina Mutiara Tsabbit (Jurnal Pengabdian Tri Bhakti, 2025)
In the current era of digitalization, many Micro, Small, and Medium Enterprises (MSMEs) have adopted various digital wallet payment methods, including the use of the QRIS payment system. Additionally, MSMEs can enhance their competitiveness by implementing systematic bookkeeping to ensure that their sales outcomes are balanced with expenses such as raw materials, operational costs, and inventory damage mitigation. This study was conducted through observation and workshops based on the real conditions in Kiaradodot Village, Gandamekar, Garut Regency, where QRIS payments and digital bookkeeping systems have not yet been implemented. The final result of this research indicates that by adopting QRIS and digital bookkeeping, MSMEs are expected to develop the skills necessary to utilize payment systems that improve customer convenience, strengthen brand image, and optimize their business potential to drive sales growth.